2007
DOI: 10.3748/wjg.v13.i16.2333
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal intraepithelial T lymphocytes in patients with functional dyspepsia

Abstract: In H pylori negative FD patients, the phenotypic characterization of IELs suggests that we cannot exclude a role of IELs in FD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 51 publications
0
27
0
Order By: Relevance
“…In contrast to Walker et al, 34 Gargala et al found no differences between duodenal IEL counts of H. pylori negative, functionally dyspeptic adults and controls. 36 One study conducted on children with functional dyspepsia 37 also noted differences in duodenal mast cell densities but not in IEL counts. In summary, although a theoretical influence of a functional gastrointestinal disorder on the presence of intestinal inflammatory cells might be argued, available studies are insufficient at this point to support an association with duodenal IELs.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to Walker et al, 34 Gargala et al found no differences between duodenal IEL counts of H. pylori negative, functionally dyspeptic adults and controls. 36 One study conducted on children with functional dyspepsia 37 also noted differences in duodenal mast cell densities but not in IEL counts. In summary, although a theoretical influence of a functional gastrointestinal disorder on the presence of intestinal inflammatory cells might be argued, available studies are insufficient at this point to support an association with duodenal IELs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Gargala et al54 reported that the number of intraepithelial lymphocytes in the duodenal mucosa was significantly greater in H. pylori -positive FD patients than in healthy controls, but not different between H. pylori -negative FD patients and healthy controls. The expressions of CD95/Fas and HLA-DR-expressing CD3 + lymphocytes were lower in H. pylori -negative FD patients than in healthy controls.…”
Section: Duodenum - a Crossroad Between Helicobacter Pylori And Dyspementioning
confidence: 99%
“…Early satiety, weight loss, nausea and vomiting are more frequently reported in patients with presumed PI-FD 53 . Helicobacter pylori ( H. pylori ) infection, gastric emptying, and gastric sensitivity do not seem to be associated with PI-FD, whereas a high prevalence of impaired gastric accommodation is observed in patients with presumed PI-FD 54. This impairment is suggested to be attributable to a dysfunction at the level of gastric nitrergic neurons.…”
Section: Duodenal Immune Activation In Fdmentioning
confidence: 99%